Posted by **sonia** on Thursday, October 22, 2009 at 8:46pm.

find the indicated outputs for f(x)= 4x-5x= f(0)=

f(-1)=

f(2)=

- algebra -
**bobpursley**, Thursday, October 22, 2009 at 9:13pm
f(-1)=4(-1)-5(-1)=1

## Answer This Question

## Related Questions

- algebra - Find the indicated outputs for f(x) =4x^2 -4x f(0) f(-1) f(2)
- algebra - Find the indicated outputs for f(x)=4x^2 -4x f(0) f(-1) f(2)
- algebra - find the indicated outputs for f(x)5^2-4x F(0)= f(-1)= f(2)=
- Algebra - Find the indicated outputs for f(x)= 5 x(2) - 4x. F(0)= f(-1)= f(2)=
- algebra - Find the indicated outputs for f(x) = 2x(2) - 2x f(0), f(1), f(2)
- Algebra - find the indicated outputs f(x)=2x^2-3x f(0)=? f(-1)=? f(2)=? help?
- algebra - find the indicated outputs for f(x)= 4x^2- 5x= f(0)= f(-1)= f(2)=
- Algebra 1 - Find the indicated outputs for f(x)=4x(2)-5x f(0)=? f(-1)=? (f(2)=?
- algebra - find the indicated outputs for f(x = 3x^2 -5x f(0)= f(-1)= f (2)=
- Algebra - Find the indicated outputs for f(x)=¡¼5x¡½^(2 )-2x f(0)= f(-1)= f(2)=

More Related Questions